Simulation and Control of Saltwater Intrusion Through Numerical and Physical Modeling Techniques - Ganfoud, Ahmed Abulaid (1997)
Simulation and control of saltwater intrusion based on hydrodynamic dispersion has been investigated through numerical and physical modeling techniques. In the mathematical formulation, two equations were derived one for water flow and the other for solute transport that were coupled through Darcy's velocity and concentration. In the numerical model formulation, Galerkin finite element approach was applied for deriving the element matrix equation through quadrilateral elements. To save memory and computation time, a pointer matrix was used to avoid storage of most of the zeros in the resulting sparse matrix. The developed model was an efficient and a rather general one such that the aquifer can be of any types with different boundary conditions and unlimited number of sources and sinks. For model verification, Henry's problem was used to compare the model results with previous studies that applied constant and velocity-dependent dispersion coefficient. The comparison showed a good agreement between the proposed model and the previous ones. Also, for simulation of saltwater intrusion the computed isochlor contours for the physical model were in good agreement with the experimental ones By using the sandbox model and other apparatuses, the average values of porosity, hydraulic conductivity, dispersion coefficient, and saltwater density were found to be 0.36, 0.0855 cm/s, 14.34, 10-2 cm2/s, and 1027. 5 kglm3 respectively. These parameters were used in the numerical simulation. Saltwater intrusion was simulated experimentally using the physical model under steady and unsteady state conditions through the measurement of the sodium chloride distribution in the aquifer. According to physical simulation, the intruded length was changed from 48 cm at steady state to 79 cm at the end of 90 minutes from the steady state during which the freshwater head was changed every 30 minutes by 0.5 cm from 50 cm to 48.5 cm.